By definition of tangent,
tan(A - π/4) = sin(A - π/4) / cos(A - π/4)
Expand the numerator and denominator using the angle sum identities for sin and cos:
tan(A - π/4) = (sin(A) cos(π/4) - cos(A) sin(π/4)) / (cos(A) cos(π/4) + sin(A) sin(π/4))
Divide through everything on the right by cos(A) cos(π/4):
tan(A - π/4) = (sin(A) / cos(A) - sin(π/4) / cos(π/4)) / (1 + (sin(A) sin(π/4)) / (cos(A) cos(π/4)))
Simplify the sin/cos terms to tan:
tan(A - π/4) = (tan(A) - tan(π/4)) / (1 + tan(A) tan(π/4))
tan(π/4) = 1, so we're left with
tan(A - π/4) = (tan(A) - 1) / (1 + tan(A))
Replace tan(A) with -√15:
tan(A - π/4) = (-√15 - 1) / (1 - √15)
Then the last option is the correct one.